POLA ASUH ORANG TUA DENGAN KEPRIBADIAN ANAK USIA 5-6 TAHUN DI PAUD ANAK BANGSA - Yenny Kurnia Fitri Harahap, Darajat Rangkuti (FKIP UMN ALWASHLIYAH, 2024)
This research aims to determine the relationship between parenting patterns and the personality of children aged 5 - 6 years in the Integrated Preschool for Children of the Nation for the 2023/2024 academic year. This research uses a quantitative approach which includes a correlation type, the population of this study is 30 children and the sample is 30 children. Because the population was less than 100, the sample was determined using a total sample of 30 children from the questionnaire and interview instrument data. Data analysis uses hypotheses using instruments and product moment correlation formulas. The results of this research show that the calculated t value is 5,434 > t table (1.701). This can be explained correctly by the r table, there is a very significant relationship between parenting patterns and the personality of early childhood children aged 5-6 years in Integrated PAUD Anak Bangsa, Penanggalan District, Academic Year 2023/2024. So with this it can be concluded that the hypothesis can be accepted.